Byron, poetics, and history - Stabler, Jane (Cambridge University, 2013)
Jane Stabler offers the first full-scale examination of Byron's poetic form in relation to the historical debates of his time. Responding to recent studies of publishing and audiences in the Romantic period, Stabler argues that Byron's poetics developed in response to contemporary cultural history and his reception by the English reading public. Drawing on extensive new archive research into Byron's correspondence and reading, Stabler traces the complexity of the intertextual dialogues that run through his work. For example, Stabler analyses Don Juan alongside Galignani's Messenger - Byron's principal source of news about British politics while in Italy - and refers to hitherto unpublished letters between Byron's publishers and his friends revealing a powerful impulse among his contemporaries to direct his controversial poetic style to their own political ends. This study will be of interest to Byronists and, more broadly, to scholars of Romanticism in general.